Ekspresja twórcza i artystyczna jako pola namysłu i empirycznych penetracji pedagogiki wczesnoszkolnej - Krasoń, Katarzyna (Chowanna, 2019)
The article presents a concept of including child expression, especially the one focused on bodily activity, in activities addressed to pupils of kindergarten and of grades 1–3 of primary school. The text begins with an outline of Maurice Merleau-Ponty’s idea of embodied subjectivity, and concludes with the characteristics of research conducted in the Department of Early Childhood Education and Media Pedagogy at the University of Silesia in Katowice. In addition, the article describes specific initiatives that have been launched in the Department, such as the creation of the Children’s Expression Centre and the organisation of Polish Expression Festivals in Katowice.